Implementing the Round Robin Cooperative Model to Improve Motivation and Creativity in IPAS Learning - Haya Uni Aldi; Hartini, Hartini; Saripuddin, Saripuddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This classroom action research investigates the effectiveness of the Round Robin cooperative learning model in improving the motivation and creativity of learning science among Grade IV students at UPT SDN Unjuruiya No. 45, Selayar Islands. The study was conducted to address students’ low engagement, limited participation, and insufficient creative expression during IPAS lessons. The research involved 12 students (6 male and 6 female) and was implemented in two cycles, each consisting of three meetings—two for instructional activities and one for assessing learning creativity. Data were collected through observation, learning motivation assessments, and creativity evaluations. Findings indicate a significant improvement in student learning outcomes following the implementation of the Round Robin model. In Cycle I, only 5 students (42%) achieved the creative category, while 7 students (58%) remained in the non-creative category. However, after refinement and continued application in Cycle II, the number of students achieving the creative category increased substantially to 11 students (92%), leaving only 1 student (8%) in the non-creative category. These results demonstrate that the Round Robin model effectively enhances student motivation, encourages active participation, and supports the development of creativity in science learning. Overall, the study concludes that cooperative learning through Round Robin provides a meaningful and engaging instructional alternative capable of improving both motivational and creative learning aspects in elementary science classrooms.